Aspectos biológicos, comportamentais e seletividade à Encarsia hispida (Hymenoptera: Aphelinidae) em Bemisia tabaci biótipo B (Hemiptera: Aleyrodidae) no algodoeiro - Oliveira, Robério de (2016)
The cotton Gossypium hirsutum is a crop that plays a role in the Brazilian economic scenario. However, the presence of insect-pests such as whitefly Bemisia tabaci B-biotype in the cotton crop increases the costs of production in due to uses of pesticides. So, one measure to reduce this use is the adoption of Integrated Pest Management (IPM) which involves a set of tactics where the biological control can be added. In this sense, we aimed to study the biological aspects and selectivity to Encarsia hispida, having as host B. tabaci B-biotype in two cotton cultivars. The search was realized in the Laboratory of Entomology of Universidade Federal da Paraíba, Campus II, Areia-PB. The study was developed addressing the aspects explained above, being divided in three articles. In the article I evaluated the biological development and parasitism of the parasitoid E. hispida in cotton cultivars. In the first experiment it was found that only female parasitoids with longevity of 24.61 and 22.61 days in „BRS H8 and „BRS Topázio‟, respectively, not differing statistically with each other. The period of biological cycle of egg to adult of the parasitoid was, numerically, 35.68 and 33.71 days in „BRS H8 and „BRS Topázio‟, respectively, not differing statistically. In the second experiment were found parasitism indexes of E. hispida around 34.33 and 29.63% in „BRS H8 and „BRS Topázio‟, respectively. The parasitoid develops satisfactorily in the two cotton cultivars. In the article II were evaluated the foraging behavior and flight test of the parasitoid E. hispida in laboratory conditions. In the first bioassay females were used to register the following variables: activity, speed and walking pattern, while in the second were used pupae of parasitoid close to emergence, where adults were classified as its position: flying, walking and no-flying. The activity, speed and walking pattern of the parasitoid showed no influences by the cotton cultivars. The parasitoid visited the quadrants of the leaves in large majority only once, totaling 112.2 quadrants in the cultivar „BRS Topázio‟. The insects classified as flying reached 79.17 and 77.85 in „BRS H8‟ and „BRS Topázio‟, respectively. In the article III we verified the toxicity effects of synthetic products to E. hispida where we applied a completely randomized design in factorial scheme. In the bioassays were used E. hispida in the pupal and adult stages, which were submitted to pulverization with the following chemical products: thiamethoxam, deltamethrin, imidacloprid e piriproxifen in the proportions 1.0 g L-1, 1.0 mL L-1, 4.0 mL L-1 e 2.5 mL L-1, respectively, being distilled water as treatment test. The insecticides thiametoxam and imidacloprid are harmless for pupal stage, however, the same are harmless to E. hispida adult stage. The insecticides delthametrin and piriproxifen are harmless to the parasitoid E. hispida.